Transition metal salts of 2-amino-3, 5-dihalopyridine - dimers: syntheses, structures and magnetic properties of (3, 5-diCAPH)2Cu2Br6 and (3, 5-diBAPH)2Cu2X6. Issue 23 (2nd December 2017) - Anagnostis, Jason; Cipi, Joris; Landee, Christopher P.; Tremelling, Grant W.; Turnbull, Mark M.; Twamley, Brendan; Wikaira, Jan L.
Abstract: Three dimeric copper(II) complexes have been prepared with the general formula bis(2-amino-3, 5-dihalopyridinium)hexahalodicuprate cuprate(II): (3, 5-diCAPH)2 Cu2 Br6 (1 ), (3, 5-diBAPH)2 Cu2 Cl6 (2 ) and (3, 5-diBAPH)2 Cu2 Br6 (3 ) [3, 5-diCAPH = 2-amino-3, 5-dichloropyridinium; 3, 5-diBAPH = 2-amino-3, 5-dibromopyridinium]. The compounds have been characterized via single crystal X-ray diffraction and temperature dependent magnetic susceptibility measurements. All three compounds crystallize in monoclinic space groups (1, C 2/ c ;2 and3, P 21 / c ) and exhibit alternating layers of hexahalodicuprate ions and organic cations. The hexahalodicuprate ions exhibit short X⋯Cu and X⋯X contacts which link the dimers into a square array. Variable temperature magnetic susceptibility data reveal strong intradimer antiferromagnetic exchange ( J  = −153, −65, −122 K for1 –3, respectively), but negligible inter-dimer magnetic exchange. Abstract :